When is Economic Growth Pro-Poor? : Experiences in Malaysia and Pakistan - Khan, Mahmood (IMF Working Papers; Working Paper ;, 2002)
This paper focuses on two central issues related to the contrasting experiences of Malaysia and Pakistan regarding poverty reduction. First, it examines the structure of economic growth and its proximate determinants in the two countries, including the initial conditions, institutional changes, and macroeconomic policies. Second, it analyzes the links between economic growth and poverty reduction, particularly focusing on public policy mechanisms to reduce poverty and inequality. Malaysia, unlike Pakistan, was able to sustain rapid economic growth with equally impressive reduction in poverty because the governments included the poverty reduction goal in national development plans and pursued policies consistent with the twin goals.